Poster Presentation as an Education tool: Use, Views and Reviews from Undergraduate Medical students - Khattri, Bhavya; Gupta, Chhavi Kiran; Garg, Manish; Ranjan, Rijul; Pant, Bhawana; Gupta, Surabhi (Indian Journal of Community Health, 2025)
Background: Medical education has entered its modern era in our country with the new NMC devised Competency Based Curriculum de-emphasizing autocratic teaching techniques and in turn replacing them with continuous stress upon critical thinking, parallel reading, creative expression and information evaluation. Aims & Objectives: 1. To assess the use of Poster Presentations as an Educational Tool for Under Graduate (UG) Medical Students. 2. To assess the views of Under Graduate (UG) Medical Students on Poster Presentation as an Educational Tool. 3. To assess the reviews of Under Graduate (UG) Medical Students on Poster Presentation as an Educational Tool. Methodology: After ethical clearance and face validity of the questionnaire students who had participated in poster competition, were asked to fill the form for study and analysis of both open and close ended questions was done. Result: The average response recorded on Likert scale was of 4.21 (± 0.65); Cronbach’s alpha for the set of questions asked was found to be 0.914 depicting excellent internal consistency and showing that the data is very much reliable. Conclusion: Academic poster competition can be an innovative teaching and learning tool for both academic and soft skills.